PENGARUH MODEL PEMBELAJARAN SCRAMBLE DENGAN MEDIA QUESTION CARD TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 5 PEDAMARAN - Dika Septiamy; Destiniar; Adrianus Dedy (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background of this research is the low learning outcomes of fourth grade students in science learning at SD Negeri 5 Pedamaran. This study aims to determine the effect of using the Scramble learning model with Question Card media on student learning outcomes at SD Negeri 5 Pedamaran. The subjects in this study were class IV SD, namely class IVA as an experimental class which was taught using the Scramble learning model with Question Card media. Class IVB as a control class is taught using conventional learning. In this study using a quantitative approach to the experimental research method. The design form of the experimental method used is the Posttest Only Control Design. In collecting data, researchers used tests and documentation. The data analysis technique used in this study is the Independent Samples Test. The results showed that the application of the Scramble learning model with Question Card media could affect the science learning outcomes of fourth grade students at SD Negeri 5 Pedamaran, where the average score in the experimental class was 70.67 and in the control class was 43.60. The conclusion in this study is that there is a significant effect of using the Scramble learning model with Question Card media on the science learning outcomes of fourth grade students at SD Negeri 5 Pedamaran.